Reduced cortical thickness in Heschl's gyrus as an in vivo marker for human primary auditory cortex - Zoellner, Simeon; Benner, Jan; Seither-Preisler, Annemarie; Seitz, Angelika; Heinecke, Armin; Wengenroth, Martina; Blatow, Maria; Schneider, Peter (Human brain mapping, 2019)
The primary auditory cortex (PAC) is located in the region of Heschl's gyrus (HG), as confirmed by histological, cytoarchitectonical, and neurofunctional studies. Applying cortical thickness (CTH) analysis based on high-resolution magnetic resonance imaging (MRI) and magnetoencephalography (MEG) in 60 primary school children and 60 adults, we investigated the CTH distribution of left and right auditory cortex (AC) and primary auditory source activity at the group and individual level. Both groups showed contoured regions of reduced auditory cortex (redAC) along the mediolateral extension of HG, illustrating large inter-individual variability with respect to shape, localization, and lateralization. In the right hemisphere, redAC localized more within the medial portion of HG, extending typically across HG duplications. In the left hemisphere, redAC was distributed significantly more laterally, reaching toward the anterolateral portion of HG. In both hemispheres, redAC was found to be significantly thinner (mean CTH of 2.34 mm) as compared to surrounding areas (2.99 mm). This effect was more dominant in the right hemisphere rather than in the left one. Moreover, localization of the primary component of auditory evoked activity (P1), as measured by MEG in response to complex harmonic sounds, strictly co-localized with redAC. This structure-function link was found consistently at the group and individual level, suggesting PAC to be represented by areas of reduced cortex in HG. Thus, we propose reduced CTH as an in vivo marker for identifying shape and localization of PAC in the individual brain.
First published: 27 October 2018
Gesehen am 03.04.2019